Towards an Integrated Evaluation of Usability, User Experience and Accessibility in Assistive Technologies - de Godoi, Tatiany Xavier; Valentim, Natasha Malveira Costa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
The development of Assistive Technologies (AT) has been growing and promoting the autonomy of their users, aiming at quality of life, accessibility, and inclusion. In this way, one of the main quality factors is the Usability, that aims at the user having a good efficiency, effectiveness, and satisfaction when using the technology. In order to improve the ATs usability, it is necessary to go through the usability evaluation. In this paper, we present a usability evaluation carried out with an AT using two different techniques, QUEST (Quebec User Evaluation of Satisfaction with Assistive Technology) and SUS (System Usability Scale). In this evaluation, regarding usability, we focused on the aspect of user satisfaction. However, we perceived that we omitted some aspects that are relevant to consider in an AT. We also observed that analyzing only the Usability concept will leave gaps in the quality criterion. This happens because an AT needs to be accessible and bring good experiences to the user. Therefore, we recommended that to meet most of the requirements of the user and the AT, there must be an evaluation that involves the concepts of usability, accessibility, and user experience together.